Studi Fenomenologi Pemberian ASI oleh Ibu Usia Remaja pada Bayi Usia 0 Sampai 6 Bulan di Desa Karangbayat Kecamatan Sumberbaru Kabupaten Jember (Adolescent Mothers Breastfeeding in 0 until 6 month infant at Karangbayat Village Sumberbaru Sub-District Jemb - Firtamaafiyah D Rohmah; Hanny Rasni; Ratna Sari Hardiani (Pustaka Kesehatan, 2016)
Human milk is the best nutrition for infant. Breastfeed adolescent mothers are population that needsspecial treatment to keep breastfeeding successfully. This study explored breastfeeding activity byadolescent mother in 0-6 month infant in Karangbayat Village Sumberbaru Sub-District JemberRegency. The research used qualitative design with phenomenological approach. Data saturationhas been reached on the sixth participant. Data was analyzed by Colaizzi method. The result found 8themes: kind of feeling, the level of feelings, causes of feeling, the kind of breastfeeding behavior,causes of non exclusive breastfeeding behavior,the sources of non exclusive breastfeedingbehavior, support factor and the belief factor. To improve exclusive breastfeeding among adolescentmother, this study suggest, health care provider must give breastfeeding counseling and education inprenatal care with family participation, a specially grandmother.Keywords: adolescent mothers, breastfeeding, qualitative study